Risk Factor Analysis for Long-Term Graft Survival Following Pediatric Kidney Transplantation: The Importance of Pretransplantation Time on Dialysis and Donor/Recipient Age Difference - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2023)
Recognizing risk factors that may negatively affect long-term graft survival following pediatric kidney transplantation is a key element in the decision-making process during organ allocation. We retrospectively reassessed all cases of pediatric kidney transplantation performed in our center in the last 20 years with the aim of determining baseline characteristics that could be identified as prognostic risk factors for long-term graft survival. Between 2001 and 2020, a total of 91 kidney transplantations in children under the age of 18 years were undertaken in our center. Early graft failure was observed in six of the 91 patients (7%). The median follow-up of the remaining 85 children was 100 months, and the overall kidney graft survival rates at 5, 10, 15 and 20 years were 85.2%, 71.4%, 46.0% and 30.6%, respectively. Small children with a body surface area of <1 m2 were significantly associated with better long-term graft survival outcomes, while adolescents aged more than twelve years showed poorer graft survival rates than younger children. Body surface area of the recipient of ≥1 m2, pretransplantation duration of the recipient on dialysis ≥18 months, hemodialysis prior to transplantation and donor/recipient age difference of ≥25 years were significantly associated with poorer long-term graft survival.
CRIS-Team Scopus Importer:2023-12-08
Keywords: age difference; children; graft survival; kidney transplantation; renal dialysis